Appendix and Uterus Metastasis of Squamous Cell Carcinoma Arising from Mature Cystic Teratoma of the Ovary - Gülşah Balık; Işık Üstüner; Recep Bedir; Ülkü Mete Ural; Mehmet Kağıtçı; Emine Seda Güvendağ Güven (Case Reports in Obstetrics and Gynecology)
Mature cystic teratoma of the ovary rarely undergoes malignant transformation. There is no consensus for a treatment modality because of the rarity of the disease. Herein we present a case of squamous cell carcinoma (SCC) arising in a mature cystic teratoma (MCT) in a 66-year-old patient. The patient underwent total hysterectomy and bilateral salpingo-oophorectomy, omentectomy, appendectomy, and bilateral pelvic + paraaortic lymph node dissection. The histopathological examination revealed malignant invasion of the appendix and uterus. The patient, who refused the continuation of treatment initiated with the administration of a single dose of cisplatin, died 5 months later because of the disease. It is imperative that gynecologists consider appendectomy in SCC arising from MCT cases.